Aging of the vascular system: proposal of preventive intervention with known natural substances - Serafino Fazio; Valeria Fazio; Flora Affuso (Exploration of Cardiology)
Our cells and, therefore, our organism, need energy to function at their best, which is mainly produced by mitochondria. These intracellular organelles generate energy from food macromolecules across the Krebs cycle by oxidative phosphorylation. Energy is developed by converting adenosine triphosphate (ATP) to adenosine diphosphate (ADP). It is essential, for adequate mitochondrial energy production in the form of ATP, to have the right number of well-functioning mitochondria and the right amount of oxygen (O2) available. Unfortunately, the aging process and the chronic diseases that arise over the years are associated with a reduction in the number of mitochondria and their insufficient functioning. Among the chronic diseases related to significant damage of the arteries with a reduction in the supply of O2, there is atherosclerosis, where the process of atherothrombosis occurs. To keep our organs well-functioning despite aging, we must therefore protect our mitochondria and arteries. This can be achieved by intervening early in prevention with a lifestyle correction and diet integration with effective natural substances or, in some cases, with drugs. Among the many natural substances that have good scientific support, we have chosen four that have demonstrated benefits in the absence of side effects and that we know best: quercetin and pyrroloquinoline quinone to stimulate mitochondrial biogenesis and mitophagy, while L-arginine and nattokinase to protect the arteries from atherothrombosis.